Does Work Well Being Affect Performance through Work Psychology in Generation Z? - Musfiroh Nur Aslam; Sidiq Permono Nugroho (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study examines the direct effects of work-life balance and psychological well-being on job performance among Generation Z employees in Central Java, Indonesia, and investigates whether employee engagement and self-efficacy mediate these relationships.Methodology: A quantitative survey was administered to 181 Generation Z respondents working in major cities of Central Java. Data were collected using a 24-item instrument and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0.Results: The findings indicate that both work-life balance and psychological well-being have significant positive direct effects on job performance. However, employee engagement and self-efficacy do not mediate these relationships, as all indirect effects were statistically non-significant.Applications/Originality/Value: This study contributes to the literature by challenging the assumed mediating roles of engagement and self-efficacy in the well-being–performance link for Generation Z in a non-Western context. It offers practical insights for organizations aiming to enhance Gen Z performance through well-being initiatives rather than traditional engagement-based interventions.